Electronic accounting & stock management system (eASM)/ Song Siow Ching - Song, Siow Ching (2006)
In these early years of 21 century, information technology is playing an important role in our lives. With the explosion of knowledge and information nowadays, information Technology must be adopted to better manage of these aspects especially to increase the quality of store data and information. And this is why Electronic Accounting and Stock Management System (eASM) come in to bring a better experience in accounting and stock management. The eASM is developed to assist the medium size company. The main objective of this system is to develop an online based web application system to store accounting information and manage item inventory control of the company, eASM is a system assists the users on better management of the accounts and stock in order to have better overview of the shared data and also provide the users with the consistent, efficient service that ensures satisfaction. The purpose of eASM system not only take into account the users friendly aspect in the development methodology but also the usability aspect. It uses user friendly graphic user interface to porived usability functions to store modified, and delete records. ASP .NET is chosen to develop eASM.This is to advantage of the ASP .NET can support VB .NET and c# that is more powerful. It's also control or event based programming that similar to VB6. Separation between logic and presentation make the system easier.